Management of severe Atopic Dermatitis. - de Prost, Y. (European Journal of Pediatric Dermatology, 2018)
The treatment of severe atopic dermatitis is reviewed. The therapeutical and side effect of cyclosporin A, photochemotherapy, thymic hormone extracts, antifungal treatment and recombinant gamma and alpha interferon are considered.